PERAN UNHCR (UNITED NATIONS HIGH COMMISSIONER FOR REFUGEES) DALAM MENANGANI MASALAH PENGUNGSI SURIAH DI YUNANI (2014 – 2019) - Subkhi, Syukron; Harmiyati, Harmiyati (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2020)
The internal conflict in Syria took place since March 23, 2011. The anti-government period held a large demonstration in Daraa, Syria. This demonstration started the internal conflict between the Syrian Government and the opposition. The opposition group is a community movement demanding the resignation of Syrian President Bashar al-Assad. The role of the UNHCR (United Nations High Commissioner for Refugees) is needed to provide protection, and effective long-term solutions for Syrian refugees in Greece. Greece is the only gateway for Syrian refugees to enter European territory, after the Balkan countries and several other European countries shut down to accept refugees. Based on this background, this research found one problem formulation, namely how the role of UNHCR in dealing with Syrian refugees in Greece. In general, UNHCR has played a role in dealing with Syrian refugees in Greece, UNHCR carried out its role as; Instrument, by enforcing the 1951 UN Convention on refugees to member states; Arena, organizes various meetings and conferences to solve refugee problems; and Independent Actors namely meeting basic needs, clothing, food and shelter as well as refugee supervision. The role of UNHCR which can be seen to be very significant in overcoming the problem of Syrian refugees in Greece is as an independent actor which from the year of UNHCR's involvement directly in the field, provided an increase in the quality of life for Syrian refugees. While the UNHCR's obstacle was in upholding UNHCR member countries' compliance with the 1951 UN Convention.